The Polyrhythmic-scape of the City - Tamao Hashimoto (Materia Arquitectura)
This paper shows the work of the 'Cosmopolitan Workshop', which is part of the Arts and Study Abroad Program (ASAP) at Tokyo University of the Arts. ASAP encourages interdisciplinarity and practical design research strategies out of